Graphs and algorithms : proceedings of the AMS-IMS-SIAM Joint Summer Research Conference held June 28-July 4, 1987 with support from the National Science Foundation - AMS-IMS-SIAM Joint Summer Research Conference in the Mathematical Sciences on Graphs and Algorithms; Richter, R. Bruce; American Mathematical Society; Institute of Mathematical Statistics; Society for Industrial and Applied Mathematics (Contemporary mathematics, 1989)
This volume contains the proceedings of the AMS-IMS-SIAM Joint Summer Research Conference on Graphs and Algorithms, held in 1987 at the University of Colorado in Boulder. The purpose of the conference was to foster communication between computer scientists and mathematicians, for recent work in graph theory and related algorithms has relied on increasingly sophisticated mathematics. Wagner's Conjecture, self-adjusting data structures, graph isomorphism, and various embedding and labelling problems in VLSI are examples of the kinds of questions now facing the field. With around 65 participants, the conference brought out the depth and diversity of current research in this area. The wide range of topics covered in this volume demonstrates the vitality of the activity in both mathematics and computer science and captures the diversity and excitement of the conference.